TransMath Innovative Solutions from Mathematical Technology - Quintela, Peregrina; Fernández, Ana Belén; Martínez, Adela; Parente, Guadalupe; Sánchez, María Teresa (Sxi — Springer per l’Innovazione / Sxi — Springer for Innovation, ISSN 2239-2688, 2012)
The book "TransMath - Innovative Solutions from Mathematical Technology" has been conceived as a tool for the dissemination of scientific knowledge. This publication is addressed to those companies with innovation needs that could be met through mathematical technology. The book maps both existing and possible interactions and connections that enable technology transfer between Spanish mathematical research and industrial and business sectors. Businesses can determine the level of implementation and demand for such technology within their sector and understand the benefits and innovations achieved in other companies and industries with the application of mathematical techniques. The information is classified into eleven sectors of economic activity: Biomedicine & Health; Construction; Economics & Finance; Energy & Environment; Food; ICT; Logistics & Transport; Management & Tourism; Metal & Machinery; Public Administration; and Technical Services.
Keywords: Mathematics; Applied mathematics; Engineering mathematics; Computer science : Mathematics; Computer mathematics; Mathematical physics; Mathematical models; Operations research; Management science; Statistics; Mathematical Modeling and Industrial Mathematics; Applications of Mathematics; Mathematical Applications in Computer Science; Mathematical Applications in the Physical Sciences; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Operations Research, Management Science; Computer science : Mathematics